Impacts of freshwater discharges from the Mekong river system on the oceanic variability off Southern Vietnam - Nguyen Kim, Cuong; Nguyen Dac, Da; Dam Hai, Song; Morimoto, Akihiko; Nguyen Ba, Thuy; Tran Anh, Tu (Vietnam Journal of Earth Sciences, 2026)
In recent years, the primary concern in the downstream region of the Mekong River system has been changes in river discharge due to climate change and the construction of upstream hydropower dams. This change might affect the salinity and productivity in the southern waters of the Mekong Delta. This study used measured water discharges, satellite ocean color, and a gridded salinity dataset from 2010 to 2020 to investigate these variations. The spatial and temporal distributions of sea surface salinity and chlorophyll a concentration have been discussed based on statistical analysis. It has been confirmed that the salinity in the Gulf of Thailand is consistently lower than that in the East Vietnam Sea. In the Mekong plume area, salinity is strongly correlated with variations in freshwater discharge. The main reasons for these distributions were discussed in this paper. It is noted that the time lag between freshwater discharges and salinity and chlorophyll a concentrations in the Mekong plume region was 1 month. In contrast, they were 5 months and 2 months in the Gulf of Thailand, respectively. It can be confirmed that Mekong River water did not play a significant role in the productivity of the Gulf of Thailand, but it is the main source of the lower salinity. In the offshore area of the Mekong plume, the impact of freshwater discharges was small in magnitude but quite apparent in phase, with a 2-month time lag between salinity and ocean color.